Mission en temps de guerre : Alfred Métraux dans le Pilcomayo - Lorena I. Córdoba (Journal de la Société des Américanistes)
The paper analyses the relationship between Alfred Métraux and the Toba and Pilagá peoples of Western Formosa (Argentina) during 1933. The peculiar sociopolitical circumstances that encompassed Métraux’s fieldwork are detailed: the logistical problems due to the feeble economic situation of University of Tucumán, the Chaco War between Bolivia and Paraguay (1932-1935), the inescapable relationship with the Anglican settlements of the South American Missionary Society and the tense situation on the national frontier between Argentina and Paraguay. By combining personal letters, published texts and oral and written sources, the paper aims to reconstruct the general context of the first ethnographic experiences of Métraux in the Gran Chaco.